2002
DOI: 10.1063/1.1426387
|View full text |Cite
|
Sign up to set email alerts
|

The retraction of the edge of a planar liquid sheet

Abstract: Our objective is to investigate the motion of a free two-dimensional edge of a liquid sheet, which recedes and accumulates fluid as it is pulled back toward the bulk of the sheet due to surface tension. In the long time limit, the velocity of this edge reaches a constant value given by Taylor [Proc. R. Soc. London, Ser. A 253, 313 (1959)] and Culick [J. Appl. Phys. 31, 1128 (1960)], independent of the fluid viscosity. The way this value is reached, however, depends on the viscosity. In order to follow quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 24 publications
8
71
0
Order By: Relevance
“…While the axial stretching of the rim, due to the radial crown expansion, decreases the amplitude of the perturbation [13], no such assumption can be made here as the planar sheet is initially ejected from the two-dimensional wave crest without any initial transverse stretching (Section 3 (f)). The longitudinal oscillation of the sheet thickness, whose amplitude decreases with the distance to the rim, have also been observed during retraction for low Ohnesorge number flows [30,31]. As yet the presence of any longitudinal oscillation has not been confirmed in the present experiments, however, the generation mechanism for the observed transverse variations in sheet thickness may be interpreted as a re-orientation of capillary waves on a thin stretched sheet [20].…”
Section: (A) Governing Equationmentioning
confidence: 39%
“…While the axial stretching of the rim, due to the radial crown expansion, decreases the amplitude of the perturbation [13], no such assumption can be made here as the planar sheet is initially ejected from the two-dimensional wave crest without any initial transverse stretching (Section 3 (f)). The longitudinal oscillation of the sheet thickness, whose amplitude decreases with the distance to the rim, have also been observed during retraction for low Ohnesorge number flows [30,31]. As yet the presence of any longitudinal oscillation has not been confirmed in the present experiments, however, the generation mechanism for the observed transverse variations in sheet thickness may be interpreted as a re-orientation of capillary waves on a thin stretched sheet [20].…”
Section: (A) Governing Equationmentioning
confidence: 39%
“…However, for highly viscous films, an alternative explanation for the absence of a rim was obtained from a hydrodynamic analysis of the flow near the edge of purely viscous liquids. 25 It was shown that the rim formation is governed by a single parameter,…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…With this simple calculation, we see the role of viscosity in the dynamics of retraction: it affects how the momentum is distributed through the film, but does not affect its terminal speed u c . As also pointed out in the two-dimensional numerical calculations of Sünderhauf et al (2002), in the long time limit, half of the surface energy is converted to kinetic energy, while the other half is ultimately dissipated through the action of viscosity.…”
Section: Conservation Lawsmentioning
confidence: 99%
“…Their results however were somewhat limited due to the short extent of the fluid sheet, and no conclusion could be drawn concerning the dynamics in the long time limit. More recently, Sünderhauf, Raszillier & Durst (2002) performed two-dimensional simulations of the Navier-Stokes equations, but neglected the ambient fluid on the basis of the prior work of Song & Tryggvason (1999). They focused primarily on exploring the acceleration phase of the film edge towards the terminal Taylor-Culick speed and provided some insights into the stability of falling liquid sheets.…”
Section: Introductionmentioning
confidence: 99%